2017
DOI: 10.1111/jav.01139
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise decreases nestlings’ metabolic rates in an urban exploiter

Abstract: High levels of anthropogenic noise produced in urban areas are known to negatively affect wildlife. Although most research has been focused on the disturbances of communication systems, chronic noise exposure can also lead to physiological and behavioural changes that have strong consequences for fitness. For instance, behavioural changes mediated by anthropogenic noise (e.g. quality of parental care) may alter development and could influence nestling phenotype. We tested if nestling metabolism was influence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…There is now considerable evidence for the negative impacts of noise levels on wild birds ( 46 48 ) such as temporary physical damage to ears ( 49 ), stress responses including increased corticosterone metabolites ( 50 , 51 ), telomere reduction ( 52 ), decreased in metabolic rate ( 53 ), decreased nestling size, and increased oxidative status ( 54 ), reduction in foraging ( 55 ), disturbance to vocal communication and risk perception ( 51 , 56 , 57 ) as well as decreased reproductive success [e.g., ( 51 , 57 , 58 )]. As the hearing range for birds significantly differs from that of rodents ( 59 ), it seems plausible that husbandry practices for rodents are not necessarily applicable for the good management of birds, including songbirds ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is now considerable evidence for the negative impacts of noise levels on wild birds ( 46 48 ) such as temporary physical damage to ears ( 49 ), stress responses including increased corticosterone metabolites ( 50 , 51 ), telomere reduction ( 52 ), decreased in metabolic rate ( 53 ), decreased nestling size, and increased oxidative status ( 54 ), reduction in foraging ( 55 ), disturbance to vocal communication and risk perception ( 51 , 56 , 57 ) as well as decreased reproductive success [e.g., ( 51 , 57 , 58 )]. As the hearing range for birds significantly differs from that of rodents ( 59 ), it seems plausible that husbandry practices for rodents are not necessarily applicable for the good management of birds, including songbirds ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Noise pollution could also directly disturb the nestlings, and as a result, increase nestling CORT secretion as previously shown in a few bird species (Kleist et al, ; Davies, Beck, & Sewall, ; but see Angelier, Meillère, Grace, Trouvé, & Brischoux, ). Previous studies have demonstrated that urban noise is associated with changes in nestlings growth, metabolism, and stress response, and with a reduced probability of survival in several bird species (e.g., tree swallows in Leonard & Horn, ; Injaian et al, ; white‐crowned sparrows ( Zonotrichia leucophrys orienta ) in Crino, Johnson, Blickley, Patricelli, & Breuner, ; house sparrows in Meillère, Brischoux, Ribout, & Angelier, ; Brischoux, Meillère, Dupoué, Lourdais, & Angelier, ; western bluebirds ( Sialia mexicana ) in Kleist et al, ). Light pollution may also result in an increase in feather CORT because it artificially increases the amount of time nestlings are active.…”
Section: Discussionmentioning
confidence: 99%
“…We quantified energy metabolism in both parents and offspring by measuring oxygen consumption rates using multichannel open-circuit respirometry (Sable Systems Int., Las Vegas, NV, United States; Brischoux et al, 2017 ). We measured offspring when they were 32 ± 2.9 (range: 28–39) days-old, and we measured parents after they had finished reproduction [75 ± 26 days after their last foster nestling reached Day 30 (for those that successfully raised at least one nestling); 102 ± 20 days since their last laid egg (all birds)].…”
Section: Methodsmentioning
confidence: 99%